Pengaruh Pengembangan Karir dan Budaya Organisasi terhadap Kinerja Melalui Kepuasan Kerja Guru Sekolah Kebangsaan Kebun Sireh Pulau Pinang - Zulkifli Rusby; Zulfadli Hamzah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
Human resource plays important role and the most dominant factors in organization. Employee performance can be measured by various indicators, one of which is job satisfaction. This research employs descriptive approach with collected primary and secondary data in describing the effect of carrier development and culture organization on teacher performance through job satisfaction. The population of this research include all teacher are 46 respondent. Data analysis technique use path analysis. The result of this research found that carrier development through job satisfaction indirectly has positive influence or significance toward teacher performance. Besides that, organizational culture through job satisfaction indirectly also has positive influence or significance toward teacher performance. Keywords: Carrier Development,Organizational Culture,Performance,Job Satisfaction, Path Analysis